HUBUNGAN PEMBERIAN KOMBINASI JUS JAMBU BIJI DAN JUS BAYAM TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL TRIMESTER II-III DI BPM YOSEPHINE PALEMBANG - Ade Marlisa Rahmadayanti; Santi Pratiwi; Yan Permadi (Jurnal Kesehatan Abdurrahman, 2021)
Anemia is a condition where the body has lack of red blood cells (erythrocytes). The red blood cells contain hemoglobin which it serve to carry oxygen throughout the body’s tissues. Data from Private Practice Yosephine in 2019 are the total of pregnancy women who anemia as 20 respondents. This purpose of the research determined the relation between giving the combination of guava juice and spinach juice to increase hemoglobin levels in pregnancy women. This design of the research was a Quasy Eksperiment with non-equivalent control-group from 20 samples of anemia of the pregnancy women. Variable independent was combination of guava juice and spinach juice, the variable dependent was a change in hemoglobin level of the pregnancy women. Data collection is using primer data by the observation sheet measuring hemoglobin level, before and after checking. The research is using t-test. The result of research was hemoglobin level of pregnancy women on treatment group increasing to 10,71 gr% from 10,16 gr%. The result of t-test with significance level α = 0,05 got ρ-value = 0,001 (ρ-value < α (0,05)), which was concluded if there was relation giving combination guava juice and spinach juice to increase hemoglobin level the pregnancy women.